Modeling the marathon and human endurance performances: some thoughts and what’s new? - Joyner, Michael J. (International Journal of Sports Medicine, 2025)
In 1991, I published a physiological model of marathon running performance. My model predicted that it might be possible for a human to run the marathon in less than 2 hours. In this article, I review the genesis of my thinking at that time, share my perspective about what has changed over the last 30 plus years, and speculate about what the future might hold.
Keywords: marathon; human performance; modeling